Enabling the sustainable recycling of LiFePO4 from spent lithium-ion batteries. Issue 6 (25th February 2022) - Qiu, Xuejing; Zhang, Baichao; Xu, Yunlong; Hu, Jiugang; Deng, Wentao; Zou, Guoqiang; Hou, Hongshuai; Yang, Yue; Sun, Wei; Hu, Yuehua; Cao, Xiaoyu; Ji, Xiaobo
Abstract : Enabling the sustainable recycling of LiFePO4 from spent lithium-ion batteries via a one-step oxidation leaching process endowed with better environmental and economic returns. Abstract : The recycling of spent lithium-ion batteries (LIBs) is a crucial issue that has engaged extensive attention worldwide, along with the rapidly increasing usage of lithium-ion batteries. State-of-art recycling approaches, in terms of chemical leaching, have imperfections such as excessive chemical consumption, tedious recycling procedure and aggravated secondary pollution. In this research, a green and closed-loop route for the recycling of spent LiFePO4 involving oxidation leaching is demonstrated. By properly adjusting or controlling the leaching parameters, the leaching efficiency of lithium is up to 97.6% with the introduction of hydrogen peroxide, which is facilitated to achieve the transformed high-purity lithium carbonate and iron phosphate. The oxidation reaction mechanisms are clarified through thermodynamic and kinetic analyses, which identified that the oxidation leaching reaction is co-controlled by the internal diffusion and chemical reaction. Consequently, LiFePO4 cathode materials are regenerated by utilizing the obtained raw materials, as expected, which deliver superior cycling stability with less than 1% of capacity loss after 300 cycles and excellent rate performances. This research embodies the possibility of efficient recycling of LiFePO4 from spent lithium-ion batteries based on the principles of green chemistry that is possibly committed to the sustainability of the lithium-ion battery industry.